2022
DOI: 10.3389/fcell.2021.825729
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypomethylation of TGFBR3 as a Risk Factor of Alzheimer’s Disease: An Integrated Epigenomic-Transcriptomic Analysis

Abstract: Alzheimer’s disease (AD) is characterized by the abnormal deposition of amyloid-β (Aβ) plaques and tau tangles in the brain and accompanied with cognitive impairment. However, the fundamental cause of this disease remains elusive. To elucidate the molecular processes related to AD, we carried out an integrated analysis utilizing gene expression microarrays (GSE36980 and GSE5281) and DNA methylation microarray (GSE66351) in temporal cortex of AD patients from the Gene Expression Omnibus (GEO) database. We total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…TGFBR3 expression was observed to be elevated in Alzheimer's disease (AD), while its promoter methylation level of cg17074213 decreased considerably. 58 In our study, we found that TGFBR3 mRNA increased in NPC cells following treatment with 5-Aza-CdR. The above results suggested that aberrant expression of TGFBR3 in NPC was associated with DNA methylation.…”
Section: Discussionsupporting
confidence: 60%
“…TGFBR3 expression was observed to be elevated in Alzheimer's disease (AD), while its promoter methylation level of cg17074213 decreased considerably. 58 In our study, we found that TGFBR3 mRNA increased in NPC cells following treatment with 5-Aza-CdR. The above results suggested that aberrant expression of TGFBR3 in NPC was associated with DNA methylation.…”
Section: Discussionsupporting
confidence: 60%
“…Adar encodes for a protein called ADAR1, and increased expression of ADAR1 has been associated with stress-induced cognitive impairment in mice [37]. Gnb1 expression engages in G-protein-coupled receptors by acting as a molecular switch in the signal transduction [38]. The increased expression of brain Gnb1, which we also observed in the DOX-only-treated mice, has been linked to anxiety and depressive behavior [39].…”
Section: Discussionmentioning
confidence: 56%
“…Doxorubicin has been shown to cause anxiety in humans and anxiety-like behavior in mice and rats [40][41][42][43]. In humans, Gnb1 expression has been shown to be increased in neurological diseases including Alzheimer's disease [38]. Lastly, Vim encodes for vimentin, which is a marker of reactive astrocytes in reactive gliosis, and its expression is increased in neurodegenerative diseases [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Hypomethylation increases with age and leads to an unstable genome, with activation of some tumor promoter genes 134,135 . Hypomethylation of CpG islands (cytosine-guanine pairs) promotes AD 136 , LBD 137,138 , and PD 139 .…”
Section: Apoe and Methylationmentioning
confidence: 99%